Numerical and experimental investigation of composite heat pipe technology - Coulson, Keith (2018)
Heat pipes are heat transport devices that pose very small thermal resistance to heat flow, even over relatively long transport paths. Utilizing two-phase heat transfer, they can transport heat from con fined spaces to remote heat sinks where more surface area might be readily available. This attribute is particularly useful in multiple thermal management applications, such as power generation, electronics cooling, and permafrost retention. To improve specific (per unit mass) performance and reduce manufacturing cost, we present here a concept for a composite heat pipe that utilizes different materials for the adiabatic and evaporator/condenser sections. Such composite heat pipes can be fabricated with low cost materials, while maximizing specific heat transfer performance. We present a mathematical model of heat transport in the composite heat pipe that accounts for the pressure driven flow of the vaporized working fluid, the pressure drop over the length of the wick, and the thermal resistances governed by the wall, wick, liquid, and vapor. We use the model to show that the composite heat pipe has the potential for identical effective thermal conductivity when compared to its all metal counterpart, with drastic improvement (~1000%) in specific performance. We further use the model to perform sensitivity analysis and parametric multi-objective design optimization with respect to specific performance maximization and cost minimization. Finally, we design and build an apparatus to experimentally test how substituting the adiabatic section metal wall with a non-metal material impacts heat pipe performance. Our work offers a design platform for the development of next generation thermal transport devices that reduce cost and weight, and maximize manufacturability. They facilitate implementation flexibility through modular design and integration schemes conducive to additive manufacturing techniques. Submission original under an indefinite embargo labeled 'Open Access'. The submission was exported from vireo on ...